Mapping neonatal mortality in India: A closer look - Myron Anthony Godinho; Shruti Murthy; Theophilus Lakiang; Amitha Puranik; Sreekumaran N Nair (Wolters Kluwer Medknow Publications, 2017)
Introduction: Fifty-three percent of Indian under-5 deaths occur during the neonatal age group. Recognizing that there is a lack of illustrated district-level data on neonatal mortality in India, we mapped this to visually highlight districts where neonatal health issues require the most attention. Methods: District-level estimates of 596 Indian districts were used to generate maps and to illustrate neonatal mortality rates (NMRs), absolute numbers of neonatal deaths; the best and worst performing districts (positive and negative deviants) in each Indian state; the neonatal female/male death ratio; and district lag in NMR reductions. Results: The NMR ranged from 4.3 (Kannur, Kerala) to 65.1 (Datia, Madhya Pradesh), with the mean NMR being 29.8. Almost two-thirds of the districts (n = 380, 63.7%) had NMRs between 20 and 40. The top third of neonatal deaths could be accounted for by just 71 districts of a total of 596. Conclusion: There is an urgent need for up-to-date data on district-level neonatal mortality in India.